2022
DOI: 10.1001/jamanetworkopen.2022.41951
|View full text |Cite
|
Sign up to set email alerts
|

Association of Coded Housing Instability and Hospitalization in the US

Abstract: ImportanceHousing instability and other social determinants of health are increasingly being documented by clinicians. The most common reasons for hospitalization among patients with coded housing instability, however, are not well understood.ObjectiveTo compare the most common reasons for hospitalization among patients with and without coded housing instability.Design, Setting, and ParticipantsThis cross-sectional, retrospective study identified hospitalizations of patients between age 18 and 99 years using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Housing insecurity has been previously implicated in higher rates of being lost to follow-up in patients with diabetic retinopathy and higher risk for treatment barriers such as medication noncompliance and delayed time to resolution in patients with infectious keratitis . In a previous large database study, the authors investigated the impact of housing insecurity on all hospitalizations in the US and found a trend toward longer LOS, although these results did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Housing insecurity has been previously implicated in higher rates of being lost to follow-up in patients with diabetic retinopathy and higher risk for treatment barriers such as medication noncompliance and delayed time to resolution in patients with infectious keratitis . In a previous large database study, the authors investigated the impact of housing insecurity on all hospitalizations in the US and found a trend toward longer LOS, although these results did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Z codes are markedly underutilized with studies consistently showing that under 1% of claims contain Z codes related to housing issues and likely are more specific rather than sensitive for housing concerns. [29][30][31] Screening questions, though also imperfect measures, have been shown to have better area under the curve scores than Z codes for housing. 32 More complete documentation of housing status, including housing instability, may facilitate a more nuanced analysis of drivers of disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Other literature has used Z codes to classify patients as unhoused. Z codes are markedly underutilized with studies consistently showing that under 1% of claims contain Z codes related to housing issues and likely are more specific rather than sensitive for housing concerns 29–31 . Screening questions, though also imperfect measures, have been shown to have better area under the curve scores than Z codes for housing 32 .…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Traumatic injury is the second leading reason for hospitalization among people experiencing homelessness. 11 A previous study 9 demonstrated that injured people experiencing homelessness are more likely to be admitted to the hospital than housed individuals. However, little is known about their subsequent hospital course and the incidence of morbidity, surgical procedures, and intensive care unit (ICU) admissions.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic injury is the second leading reason for hospitalization among people experiencing homelessness . A previous study demonstrated that injured people experiencing homelessness are more likely to be admitted to the hospital than housed individuals.…”
Section: Introductionmentioning
confidence: 99%